Tuning, Impedance Matching, and Temperature Regulation during High-Temperature Microwave Sintering of Ceramics - Sylvain Marinel; Nicolas Renaut; Etienne Savary; Rodolphe Macaigne; Guillaume Riquet; Christophe Coureau; Thibault Gadeyne; David Guillet (Advances in Materials Science and Engineering)
Over the years, microwave radiation has emerged as an efficient source of energy for material processing. This technology provides a rapid and a volumetric heating of material. However, the main issues that prevent microwave technology from being widespread in material processing are temperature control regulation and heating distribution within the sample. Most of the experimental works are usually manually monitored, and their reproducibility is rarely evaluated and discussed. In this work, an originally designed 915 MHz microwave single-mode applicator for high-temperature processing is presented. The overall microwave system is described in terms of an equivalent electrical circuit. This circuit has allowed to point out the different parameters which need to be adjusted to get a fully controlled heating process. The basic principle of regulation is then depicted in terms of a block function diagram. From it, the process has been developed and tested to sinter zirconia- and spinel-based ceramics. It is clearly shown that the process can be successfully used to program multistep temperature cycles up to ∼1550°C, improving significantly the reproducibility and the ease of use of this emerging high-temperature process technology.